The Immune Response to SARS-CoV-2 Vaccination: Insights Learned From Adult Patients With Common Variable Immune Deficiency - Quinti, Isabella; Locatelli, Franco; Carsetti, Rita (Frontiers in Immunology, 2022)
CVID patients have an increased susceptibility to vaccine-preventable infections. The question on the potential benefits of immunization of CVID patients against SARS-CoV-2 offered the possibility to analyze defective mechanisms of immune responses to a novel antigen. In CVID, as in immunocompetent subjects, the role of B and T cells is different between infected and vaccinated individuals. Upon vaccination, variable anti-Spike IgG responses have been found in different CVID cohorts. Immunization did not generate Spike-specific classical memory B cells (MBCs) but atypical memory B cells (ATM) with low binding capacity to Spike protein. Spike-specific T-cells responses were also induced in CVID patients with a variable frequency, differently from specific T cells produced after multiple exposures to viral antigens following influenza virus immunization and infection. The immune response elicited by SARS-CoV-2 infection was enhanced by subsequent immunization underlying the need to immunize convalescent COVID-19 CVID patients after recovery. The search for a strategy to elicit an adequate immune response post-vaccination in CVID patients is necessary. Since reinfection with SARS-CoV-2 has been documented, at present SARS-CoV-2 positive CVID patients might benefit from new preventing strategy based on administration of anti-SARS-CoV-2 monoclonal antibodies.